The language of memory in a crosslinguistic perspective - Amberber, Mengistu, 1961- (Human cognitive processing ;, 2007)
This book offers, for the first time, a detailed comparative study of how speakers of different languages express memory concepts. While there is a robust body of psycholinguistic research that bears on how memory and language are related, there is no comparative study of how speakers themselves conceptualize memory as reflected in their use of language to talk about memory. This book addresses a key question: how do speakers of different languages talk about the experience of having prior experiences coming to mind ('remembering') or failing to come to mind ('forgetting')? A complex array of.